The Adequacy of Phosphorus Binder Prescriptions Among American Hemodialysis Patients - Huml, Anne M. (2012)
Because hemodialysis treatment has a limited ability to remove phosphorus, dialysis patients must restrict dietary phosphorus intake and use phosphorus binding medication. Among patients with restricted dietary phosphorus intake (1000 mg/d), phosphorus binders must bind about 250 mg of excess phosphorus per day and among patients with more typical phosphorus intake (1500 mg/d), binders must bind about 750 mg per day. To determine the phosphorus binding capacity of binder prescriptions among American hemodialysis patients, we undertook a cross-sectional study of a random sample of in-center chronic hemodialysis patients. We obtained data for one randomly selected patient from 244 facilities nationwide. About one-third of patients had hyperphosphatemia (serum phosphorus level > 5.5 mg/dL). Among the 224 patients prescribed binders, the mean phosphorus binding capacity was 256 mg/d (SD 143). 59% of prescriptions had insufficient binding capacity for restricted dietary phosphorus intake, and 100% had insufficient binding capacity for typical dietary phosphorus intake. Patients using two binders had a higher binding capacity than patients using one binder (451 vs. 236 mg/d, p <0.001). A majority of binder prescriptions have insufficient binding capacity to maintain phosphorus balance. Use of two binders results in higher binder capacity. Further work is needed to understand the impact of binder prescriptions on mineral balance and metabolism and to determine the value of substantially increasing binder prescriptions.